How Should We Estimate the Performance Effect of Management? Comparing Impacts of Public Managers' and Frontline Employees' Perceptions of Management. Issue 1 (1st January 2018) - Favero, Nathan; Andersen, Simon Calmar; Meier, Kenneth J.; O'Toole, Laurence J.; Winter, Søren C.
ABSTRACT: Many areas of public management research are dominated by a top-focused perspective in which emphasis is placed on the notion that managers themselves are usually the best sources of information about managerial behavior. Outside of the leadership literature, managers are also the typical survey respondents in public management studies. An alternative perspective on management can be provided by subordinates' perceptions of what management is doing. Surveys of subordinates and of managers each pose potential advantages and potential disadvantages when it comes to measuring management, and each approach is likely to prove more fruitful for measuring certain management functions. Using a unique data set of parallel surveys on management with managers and their subordinates as respondents, we examine the differences and relationships between Danish school managers' and teachers' perceptions of management functions and the implications of such relationships for organizational performance. We find a surprisingly low correlation between manager and teacher responses regarding the same management functions. Teacher responses are better predictors of student performance for management aspects that are visible to and mediated by teachers. However, manager responses better predict performance for manager expectations that are less visible to employees.